(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In the article, onomastic conversion (lexico-semantic method) is nominative, i.e. functional transfer of words is a common phenomenon in the language, in which a lexeme is transferred from one group of words to another group of words, the transition of appellative vocabulary to a noun without any constructive means of thinking.